Family board ownership, generational involvement and performance in family SMEs - Amaia Maseda; Txomin Iturralde; Gloria Aparicio; Lotfi Boulkeroua; Sarah Cooper (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose In order to deepen our knowledge of governance of family firms, the purpose of this paper is to focus our attention on the relation between family owners who are members of the board of directors and firm performance. Also, this study sheds more light on how the generation in charge of the family firm affects that relationship, as generational involvement may be a unique predictor of governance behavior in these firms. Design/methodology/approach The authors applied a cross-sectional ordinary least squares regression model to test the hypotheses on a sample of 313 non-listed Spanish family SMEs. The authors suggest the possibility of a non-linear relationship between the percentage of ownership by family members of the board of directors and firm performance, and specifically, the authors propose an S-shaped effect that implies two breakpoints. Findings The authors find not only that an inverted U-shaped relationship exists, but also an S-shaped relationship between family board members' ownership and firm performance in family SMEs. Nevertheless, the results are different in comparing first-, second- and later-generation family firms. Originality/value This is one of the few empirical studies that examine the relationship between family board ownership and firm performance in the context of non-listed family SMEs. The authors consider that the influences of family directors on the board of directors as well as the concentration of family ownership on the board of directors are worth studying in non-listed family SMEs. Moreover, previous studies have focused mainly on large listed family firms but not on unlisted ones.
Keywords: 650; Ownership; SME; Generation; Performance; Board of directors; Agency theory; Family firm; Family board ownership